PROFITABILITAS, AGRESIVITAS PAJAK DAN KINERJA LINGKUNGAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Ramadhan, Abid; Amrin, Arfan (Economos : Jurnal Ekonomi dan Bisnis, 2019)
As far as the presence of CSR in Indonesia from 1980 to the present, the effectiveness and efficiency of CSR fund management still have many shortcomings in its implementation. This is because the motivation for disclosure of CSR in Indonesia is suspected only to maintain a good reputation for shareholders. Besides, with the issuance of Law Number 40 of 2007 concerning the obligations of Limited Liability Companies, companies are considered to only comply with these government regulations.The purpose of this study was to examine the effect of Profitability, Tax Aggressiveness and Environmental Performance as an independent variable on Corporate Social Responsibility Disclosure as the dependent variable. The population in this study are companies registered in the Jakarta Islamic Index (JII) during the period 2013-2017. Data collection techniques using purposive sampling method. Data were analyzed using multiple linear regression. The results of this study indicate that Tax Profitability and Aggressiveness do not affect Corporate Social Responsibility Disclosure while Environmental Performance affects Corporate Social Responsibility Disclosure.